PPD ACT: an app-based genetic study of postpartum depression. Issue 1 (December 2018) - Guintivano, Jerry; Krohn, Holly; Lewis, Carol; Byrne, Enda; Henders, Anjali; Ploner, Alexander; Kirk, Katherine; Martin, Nicholas; Milgrom, Jeannette; Wray, Naomi; Sullivan, Patrick; Meltzer-Brody, Samantha
Abstract Postpartum depression (PPD) is one of the most frequent complications of childbirth and particularly is suited to genetic investigation as it is more homogenous than major depression outside of the perinatal period. We developed an iOS app (PPD ACT ) to recruit, consent, screen, and enable DNA collection from women with a lifetime history of PPD to sufficiently power genome-wide association studies. In 1 year, we recruited 7344 women with a history of PPD and have biobanked 2946 DNA samples from the US. This sample of PPD cases was notably severely affected and within 2 years of their worst episode of PPD. Clinical validation was performed within a hospital setting on a subset of participants and recall validity assessed 6–9 months after initial assessment to ensure reliability of screening tools. Here we detail the creation of thePPD ACT mobile app including design, ethical, security, and deployment considerations. We emphasize the importance of multidisciplinary collaboration to correctly implement such a research project. Additionally, we describe our ability to customize thePPD ACT platform to deploy internationally in order to collect a global sample of women with PPD.